Towards taming the labor-management frontier: A strategic marketing framework - Higgins, Susan H. (Journal of business ethics, 1996)
Turbulent changes in the American business landscape over the past several years present a potentially ominous future for our society. The confluence of corporate downsizing, declining unionism and the surging preference for hiring part-time/temporary workers poses a threat to the very existence of our blue-collar middle class. Furthermore, when these conditions are juxtaposed against prevailing corporate rhapsodies to employee participation programs and a teamwork approach to quality improvement, the scenario becomes absurd., Solutions to the societal and workplace problems we face require both ethical and practical attention. This paper examines current labor-management hostilities from the Mutual Trust perspective on morality. Furthermore, I propose a strategic internal marketing framework as one mechanism for trust-building at the labor-management frontier. The premise for the study is that as a society we will be better off with the system of checks and balances which labor unions can provide; that positive business performance will result from cooperative rather than adversarial relations; and that to be a premier player in the global economy, we must replace worker cynicism and detachment with hope.